Representation of Indonesian Athletes with Disabilities in a Photo Essay by the National Photojournalism Agency Antara Foto (a Semiotic Analysis of Roland Barthes) - hapsari, dian; Trimukti, Achmad Septian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This article examines the representation of Indonesian athletes with disabilities in a photo essay documenting their intensive training for the Tokyo 2020 Paralympic Games. This study analyses the messages in a series of photo essays by Mohammad Ayudha, a photojournalist from the national news agency, Antara Foto. This research employs a descriptive qualitative approach, using Roland Barthes' semiotic analysis, to interpret the denotative, connotation, and mythical meaning in the photo essay. The findings reveal that, through his photo story sequence, photojournalist Mohammad Ayudha visualized the fighting spirit of Indonesian athletes with disabilities. Out of the thirteen photographic series, six images illustrate Roland Barthes' theory of the three stages of semiotics. These stages are designated as denotation, connotation, and myth. This study examines how photography of national athletes with disabilities during training sessions represents nationalism and determination before the 2020 Tokyo Paralympics, using Roland Barthes' three semiotic stages. The Photojournalist intends to create a photograph that conveys a message to the public that physical limitations are not an obstacle in achieving success in the field of international sports, and is expected to help eliminate negative stigma against the disabled community.